Analisis Penerapan Metode Material Requirement Planning (MRP) dalam Perencanaan dan Pengendalian Bahan Baku pada PT. BSM - Gina Hidayatul Kamila; Ade Momon (Industrika : Jurnal Ilmiah Teknik Industri, 2024)
PT. BSM, is a company that operates in the manufacturing sector by producing Mechanical Seals and is also a distributor of the Nippon Pillar Japan brand. Production planning and control is necessary to ensure that all processes function smoothly and production efficiency and effectiveness are achieved. PT.BSM's production system implements Make To Order (MTO), in which production activities are carried out when the customer places an order. This process will take place from raw materials, and semi-finished goods to finished products. This will pose a risk to the production process if the raw materials to be produced are not yet available. So it is necessary to have an analysis of planning and inventory control to expedite the production process. Therefore, the purpose of this study is to plan and control raw materials in accordance with requests from customers in the future using the Material Requirement Planning (MRP) method with the Lot For Lot (LFL) technique, after calculating the MRP with The Lot For Lot (LFL) technique obtained the planning results for mechanical seal raw material requirements for 2023 every month. Based on MRP calculations using the Lot For Lot technique, mechanical seal raw materials can be planned and controlled for the next 12 periods.            Key Words: LFL, Mechanical Seals, MRP,  Supplies